Esophageal Granular Cell Tumors Can Be Differentiated from Leiomyomas Using Endoscopic Ultrasonography - Iwamuro, Masaya (Intern Med, 2018)
OBJECTIVE: Although esophageal granular cell tumors have been reported to present as hypoechoic tumors, we noticed that their echogenicity is similar to that of the submucosal layer. We investigated the sonographic features of esophageal granular cell tumors and the diagnostic accuracy of the features. METHODS: Seven patients with esophageal granular cell tumors who underwent endoscopic ultrasonography were retrospectively reviewed. Thirteen patients with esophageal leiomyoma were selected as historical control subjects. The brightness of the tumor on ultrasonography images was measured and the echogenicity was standardized according to the echogenicity of the proper muscle and submucosal layers. Ten board-certified endoscopists then independently evaluated the endoscopic pictures of the 20 patients (Test 1), as well as the endoscopic ultrasonography images together with endoscopic pictures of the same patient set (Test 2). RESULTS: The standardized echogenicity in granular cell tumors was significantly higher than that in leiomyomas. The diagnostic accuracy of the 10 evaluators using endoscopic pictures alone (Test 1) was 72.0%. The addition of endoscopic ultrasonography images (Test 2) significantly improved the accuracy to 93.0%. CONCLUSION: The echogenicity of granular cell tumors was similar to that of the submucosal layer, and it was significantly higher than that of leiomyomas. Endoscopic ultrasonography images facilitate the accurate identification of esophageal granular cell tumors.